The Dynamics of Changing Comparative Advantage in ASEAN-4: Flying Geese Model - Iis Dwi Permatasari; Regina Niken Wilantari; Endah Kurnia Lestari (MediaTrend, 2019)
Globalization makes all the economic activities of the country becomes more open. Trade openness leads to increasingly fierce competition conditions and then raises a competitiveness. This competitiveness is the key for each country to develop products to be exported. Competitiveness is one of the criteria that determine the success of a country in international trade. This study aims to analyze the dynamics of changes in comparative advantages occurring in ASEAN-4 countries (Indonesia, Philippines, Malaysia and Thailand) in 1989 to 2016 using Product Mapping method which combines calculations between RSCA and TBI in each product classification. The results show that each country has different comparative advantages, including Indonesia which has a comparative advantage for unskilled-labor product classification (TPT and garment) and on primary product (oil and its derivative products) and is the leader for both products. Then the Philippines has a comparative advantage for the classification of technology intensive products (electronics) which is also a leader in the product. In addition, the results of research also found a change in comparative advantage as well as product specialization, including Thailand which no longer has a comparative advantage on human-capital intensive products (rubber and derivative products) but still a net-exporter. So it is with Indonesia who no longer has a comparative advantage on natural-resource products (lead) but still a net-exporter.